A, Manajemen ANALISIS MANAJEMEN SISTEM PELAYANAN KEGAWATDARURATAN OBSTETRI DI PUSKESMAS PONED WILAYAH KABUPATEN KUPANG TAHUN 2011 - TIRZA VIVIANRI ISABELA TABELAK (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
PONED Health Center is a health center that has the facilities and the ability to provide services to tackle case of emergency obstetric and neonatal care for 24 hours. Kupang district has 5 health centers capable PONED. Generally, this study aims to describe the management system of emergency obstetric care at the PONED health center Kupang regency in 2011. This is a qualitative research method. Subjects were PONED doctor, chief health center, head of environmental health and postpartum mothers pathology. The data was collected through indepth interviews, observations using the check list and study documentation. The results showed that the management of emergency obstetric care system of planning, organizing, implementation and evaluation has not been running well because there are still aspects of the input limitations include human resources, finance, facilities, legal basis, Standard Operating Procedures or SOP, guidelines,technical guidelines, as well as stakeholders. Human recourses or team PONED not stay at the health center, learning tasks, there are doctors who are from other health centers, health centers do not even have a doctor. Finance is reserved for activities PONED not exist. Most of the infrastructure has not met the standards. The legal basis in the form of a decree legalizing PONED team perform not action, which is available only Standard Operating Procedures or SOP that must be carried out every team in service. Government support is not optimal. Donor agency is also limited. Health distric who always supported health centers so impressed that more health personnel work. The policies of Comunnity Health Centre PONED already contained in the Governor Regulation Number 42 Year 2009 on Mother and Child Health Revolution. Management system of emergency obstetric care at the health center PONED Kupang regency can be run either by way of setting up as needed number, competence and qualifications, there are funds specifically designated for basic emergency services, there is a decree legalizing PONED team to provide services at the health center, the job description clear, coordination, guidance, mobilization and evaluation by involving local governments and the realignment of the revolution policies regarding human resources, finance and infrastructure and create local regulations regarding the administration of mother and child health revolution.